Kondisi Ekonomi Orang Tua dan Kelangsungan Pendidikan Anak Pasca Wajib Belajar 9 Tahun; Masihkah Searah? - Islam, Muhammad Fajrul (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
The socio-economic situation of the family plays a role in children's development. This research seeks to analyze more deeply the relationship between parents' economic conditions and the continuity of children's education after 9 years of compulsory education in Pasrepan, Pasrepan District, Pasuruan Regency. This research was conducted using a quantitative research approach. The type of research used is correlational research, namely research intended to determine whether there is a relationship between two or several variables. The results of the research show that parents' economics are related to the continuity of children's education after 9 years of compulsory education. It is proven that as many as 19 respondents who were classified as high level had their children continue to high school. Meanwhile, only 2 respondents classified as low level had their children continue to a high school level and 8 low level economic respondents had their children not continue to a high school level. From this presentation it can be concluded that the biggest reason parents face in sending their children to school is cost. Apart from the lack of costs, the author also found that